Coming of Age Through Bande dessinée: An Interview with Michel Kichka. Issue 2 (1st September 2021) - Louwagie, Fransiska; Lambert, Simon
Abstract: This interview with Belgian-Israeli graphic novelist and political cartoonist Michel Kichka covers his growing up in Belgium during the Golden Age of bande dessinée . The author discusses his early readings and influences, as well as the development of his own career in teaching and drawing. The discussion focuses in particular on the creation and publication of his graphic novels Deuxième Génération [ Second Generation ] and Falafel sauce piquante [Falafel with Spicy Sauce], published in 2012 and 2018. These works foreground essential questions about Kichka's experience as a second-generation Holocaust survivor and about his relationship with Israel. Taking an international perspective, the interview sheds further light on the emergence of the comics medium in Israel and the transnational reception of Franco-Belgian bande dessinée . It also considers Kichka's work and engagement as a political cartoonist. Interview conducted via email, following Michel Kichka's keynote at the "Tradition and Innovation in Franco-Belgian bande dessinée" conference.